Characterization of induced seismicity patterns derived from internal structure in event clusters. Issue 5 (27th May 2017) - Goertz‐Allmann, B. P.; Gibbons, S. J.; Oye, V.; Bauer, R.; Will, R.
Abstract: microseismicity induced by CO2 injection at Decatur, Illinois, occurs in distinct clusters and shows no obvious correlation with the proceeding pressure front. We analyze some of these clusters in more depth by using a waveform cross‐correlation approach. With this approach we can associate about 1400 events from two clusters, with moment magnitudes between 1.1 and −1.7, with specific formations of much smaller vertical dimensions (tens of meters) than the depth resolution of traveltime‐based event locations. The differentiation of reservoir and basement events, and the definition of subclusters by waveform correlation, rather than by location, helps to better analyze the spatiotemporal evolution of the events within a cluster. In the Decatur case, this is characterized by event migration from the reservoir into the adjacent basement. The spatial variation of Brune stress drop and Gutenberg b value exhibits signs of a fluid‐driven triggering mechanism at the cluster level, revealing a punctual hydraulic connection between reservoir and basement, most likely associated with basement faults cutting into the reservoir. The observed clustering of microseismicity can thus be explained by the lateral heterogeneity of permeability and crustal strength and is overall consistent with a pressure‐induced triggering mechanism. Hence, proper long‐term risk mitigation for large‐scale fluid injection close to the basement requires prior mapping of small subseismic basement‐connected faults. Key Points: Punctual hydraulic connection between reservoir and basement found in induced seismicity at Decatur CO2 sequestration site Waveform cross correlation can improve relative depth resolution of microseismicity enabling more in‐depth characterization Physical and statistical source parameter analysis reveals compartmentalized fluid‐driven behavior of seismicity